PENGARUH TRAIT MINDFULNESS TERHADAP COMPULSIVE BUYING PADA PENGGUNA SHOPEE USIA DEWASA AWAL - Afif, Nur; Awaluddin, Andi Sopy; Al-Fadly, Muh Wahyu (Jurnal Ilmiah Global Education, 2023)
Compulsive buying is a shopping behavior that is carried out by individuals but is detrimental with negative impulses that are carried out repeatedly to eliminate feelings of temporary satisfaction. Therefore, mindfulness is needed for individuals to realize the necessary actions. This study aims to determine the effect of mindfulness on compulsive buying in shopee users in early adulthood. The population in this study are shopee users who are in their early adulthood. The sampling technique used is accidental sampling with a total of 211 participants. The study was conducted using the Edwards Compulsive Buying Scale (ECBS) and The Mindful Attention Awareness Scale (MAAS). The results show that there is an influence of positive mindfulness on compulsive buying, which means that the more individuals have a high mindfulness trait, the more aware they will be of the psychological condition they are experiencing, in this case the difficulties they experience, so they find ways to reduce the pressure by compulsive buying behavior temporary.